Moved up and to the right
Moved up and to the left
Moved down and to the left
Moved down and to the right
Assuming you are concerned with the translation of
.. y = -1/(5x^2)
.. y = -1/(5(x+5)^2) + 2
you will find that the curve has moved up (by 2) and to the left (by 5).
When you start with y = f(x) and apply the transformation
.. y-k = f(x-h)
you will find that the point that was the origin on the original curve has moved to (h, k) on the translated curve. Of course, the translated expression is equivalent to
.. y = f(x-h) + k
Your problem has (h, k) = (-5, 2), which point is left and above the origin (0, 0).